Nonlinear Dynamic Buckling Behavior of Axially Loaded Functionally Graded Graphene-Enhanced Composite Laminated Cylindrical Shells in Thermal Conditions - Hasan, Hamad M.; Alkhfaji, Saad S. (Journal of Applied Nonlinear Dynamics, 2026)
The current paper is concerned with dynamic buckling response of axially loaded graphene-enhanced composite (GEC) laminated cylindrical shells under the influence of thermal conditions. Graphene layers are arranged in a functional graded (FG) along the direction of the shell thickness. A modified Halpin-Tsai approach is utilized to estimate the material properties of GECs and these properties are considered to be temperature dependent. Theoretical Framework is conducted based on the shear deformation theory (SDT) in conjunction with the von-Kármán relation and imperfection geometric effect. By utilizing Galerkin manner in concurrent with the Airy’s stress function, the derived nonlinear partial differential equations are solved numerically using the fourth-order Runge–Kutta manner. Budiansky–Roth standard is used to predict the dynamic buckling loads. Besides, a specific study was executed to detect the effect of graphene sheets distribution type, temperature, loading rate, imperfection geometric parameter and the geometric parameter on the GECs laminated cylindrical shells. The proposed method was validated via comparing the results obtained with those from other published ones.